Net community production, nutrients and hydrographic parameters in the South China Sea in October 2014 and June 2015 - Chuan Qin; Guiling Zhang; Zheng Wenjing; Han Yu; Liu Sumei (PANGAEA, 2023)
Net community production (NCP) corresponds to the difference between photosynthesis and respiration and can be estimated based on the dissolved oxygen to argon ratio (O2/Ar) in the mixed layer. NCP is also an important proxy for the biological pump in the ocean. In order to figure out the influencing factors on NCP and its seasonal variation in the northern slope region of the South China Sea (SCS), we conducted high-resolution underway measurements of O2/Ar and hydrographic parameters using membrane inlet mass spectrometry and multi-parameter water quality logger in the northern slope region of the South China Sea (SCS) in October 2014 and June 2015, assisted by nutrient measurement. Net community production (NCP) in the mixed layer was estimated using the supersaturation of O2/Ar (Delta O2/Ar) and gas transfer velocity (k). All the underway data were compiled into the 5-min interval. Surface water samples for the nutrient analysis were collected from Niskin bottles mounted on the conductivity–temperature–depth (CTD) instrument at sampling stations, the nutrients were then photometrically determined by an auto-analyzer. The mixed layer depth (MLD) and the euphotic depth (Zeu) were calculated at stations where CTD casts were made based on potential density and chlorophyll fluorescence respectively.